Instructional Management for Coastal Literacy: How School Principals Optimize Reading Habituation and Higher-Order Thinking Skills - Arum Muslikah; Ahmad Suriansyah (Assyfa Learning Journal, 2026)
Building a strong literacy culture in coastal schools requires strategic leadership to overcome geographical and resource limitations. This study aims to analyze how the school principal optimizes instructional management to improve coastal literacy, focusing on reading habituation and Higher-Order Thinking Skills (HOTS) at SMPN 3 Satu Atap Angsana. A qualitative case study approach was employed, with data gathered through interviews, observation, and documentation, and analyzed using the Miles and Huberman model (data reduction, data presentation, and conclusion drawing). The results revealed that the principal successfully optimized instructional management through structural policies, a mandatory 15–20 minute pre-learning reading habituation, the integration of HOTS-based literacy into the learning process, program supervision, and periodic evaluations. This collaborative initiative actively engaged the vice principal, librarians, teachers, counselors, and parents. Despite coastal constraints, these strategies successfully fostered a positive literacy culture, significantly enhancing students' reading interest, analytical skills, and learning participation. Crucially, this optimization led to a measurable increase in literacy achievements on the school’s 2023–2025 Education Report Card. In conclusion, the principal’s instructional management plays a pivotal role in establishing a contextual, sustainable literacy culture that enhances higher-order thinking in coastal educational settings.